(untitled) (Indian Journal of Nematology, 2024)
Investigations were carried out to explore the prey range, prey preference, and predation efficiency of Fictor composticola. The experiments were conducted in the laboratory of the Department of Nematology, CCS HAU, Hisar, in 1% water agar plates (5 cm dia.) at room temperature in a Completely Randomized Design. Prey range of F. composticola was studied for 12 prey nematodes viz., Aphelenchus avenae, Aphelenchoides swarupi, Ditylenchus myceliophagus (mycophagous); Panagrolaimus sp., Bursilla sp., Rhabdolaimus sp., Aerolaimus sp. and Tylencholaimus sp. (microbivorous); Heterodera avenae males and Hoplolaimus sp. (plant parasitic), Aporcelaimium sp. and Nygolaimus harishi (predator). F. composticola fed on all the prey nematodes tested. It consumed the maximum number of D. myceliophagus and a minimum number of Panagrolaimus sp. The prey preference was tested in 1% agar plates in combination of two, three and four prey nematode species, using an equal number of each prey. F. composticola preferred D. myceliophagus the most, followed by A. avenae. Bursilla sp. was the least preferred species in all the prey combinations. The effect of prey density on predatory efficiency was tested with 100, 200, 400, 800 and 1600 prey nematodes along with two males and two females of the predator. The population of prey consumed and F. composticola were recorded 24 and 48 hrs of release. The predation efficiency increased with the increase in the prey density levels, being highest at 1600 and lowest at 100. However, the per cent consumption was highest at 200 level of prey density.